Care staff perspectives of clinically meaningful outcomes for dementia residents - Alaine E. Reschke‐Hernández; Martina Vasil; Emma King; Carson Woolums (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Non‐pharmacological complementary and supportive care programs (CSCP, e.g., music therapy) are provided in addition to standard medical care for persons with dementia (PWD). Care staff observations are critical in assessing the clinical impact of CSCP on PWD. However, little is known about care staff experiences of CSCP and what factors influence documentation of outcomes. We sought to understand how care staff in Kentucky describe the clinically meaningful impact of CSCP on residents and themselves and learn what conditions enable and prohibit documentation. METHODS Four care staff from four dementia care facilities in Kentucky (representing non‐profit, for‐profit; rural, suburban, and urban areas) participated in this qualitative multiple case study. Participants were selected to reflect diverse care roles, identities, and experience. We collected data from eight semi‐structured interviews (two per participant), 24 journal entries, four observations, photographs, and publicly available facility data. The use of multiple data types helped triangulate findings and enrich the analysis. Data were coded and analyzed for emerging themes. RESULTS Participants described CSCP as enhancing residents’ holistic well‐being and being person‐centered. CSCP also improved participants’ well‐being and enhanced their sense of purpose. Primary documentation barriers were lack of time, prioritizing resident care over documentation, and top‐down regulations. Technology both enabled and prohibited documentation, with routine being a key facilitator. DISCUSSION Our findings indicate that CSCP improve PWD's quality of life by fostering engagement, joy, and personalized care, consistent with person‐centered care principles. Staff also benefit from reduced stress and improved morale. However, barriers exist, including time constraints and documentation challenges. Results may inform directions for future research, translation of CSCP from research to practice, and feasible measurement of clinically meaningful outcomes. The study underscores the importance of addressing systemic issues and advocating for policies that support sustainable, quality dementia care while enhancing both resident and staff well‐being. Highlights Care staff view person‐centered care programs as vital for residents' well‐being. Complementary programs reduce burnout and boost morale in demanding care settings. Feasible documentation is crucial to track meaningful outcomes within time limits. Results emphasize the need for policies that support care staff and quality care.